Parent-Adolescent Sexual and Reproductive Health Communication Is Very Limited and Associated with Adolescent Poor Behavioral Beliefs and Subjective Norms: Evidence from a Community Based Cross-Sectional Study in Eastern Ethiopia. - Yadeta Dessie; Yemane Berhane; Alemayehu Worku (PLoS ONE, 2015)
While parent-adolescent sexual and reproductive health (SRH) communication is one potential source of SRH information for adolescents, it appears to be inadequately practiced in Ethiopia. This study was designed to investigate the factors that limit or improve parent-adolescent SRH communication in Harar, Eastern Ethiopia.A community based cross-sectional study was done on 4,559 adolescents of age 13-18. SRH communication was measured using a nine-item scale whose response ranged from "not at all" to "always." Summated composite score ranging from 0-36 was generated; higher score indicates high SRH communication. A median value of the composite score was 4 out of the possible 36 with an Interquartile Range (IQR) of 7. Respondents were ranked as very poor, poor and satisfactory communicators based on 33rd and 67th percentiles values. Generalized ordered logit model was applied to investigate the factors associated with SRH communication.Results showed that the adolescents who were more likely to practice poor-very poor/very poor SRH communication were those who had poor behavioral beliefs on and poor subjective norms of communicating sexual issues with parents and those who perceived their parents' reproductive health (RH) knowledge as poor. Nonetheless, the probability of poor-very poor/very poor SRH communication was less with high adolescent-parent communication quality, television co-viewing and discussions, and self-disclosure.Curtailing the adolescents' underlying poor beliefs and norms, and improving adolescent-parent communication quality, self-disclosure, and television co-viewing and discussions are essential to engage the parents in sexual and reproductive health education of the adolescents.